Numerical Simulation and Comparison of Flow Characteristics in 180 Divergent and Uniform Open-Channel Bends Using Experimental Datas - Rasol Ghobadian; Kamran Mohammadi; Ali Hossain Zadeh Dalir (علوم و مهندسی آبیاری, 2009)
Few rivers running on straight paths are seen in nature; most of them have meandrous form. For meandering rivers, the flow pattern is highly complex and flow mechanics has specific characteristics at bends, which not observed on straight paths. Numerical models can be used as an effective tool for predicting such flow fields. Since all river bends do not have a uniform with, the numerical model SSIIM 3-D was used to simulate 180 bends, one with a uniform (0.6 m) width and other with a divergent (0.6 m to 0.75 m) width. Flow characteristics such as streamwise and vertical velocity profiles, primary and secondary flows, streamwise and spanwise slopes of water surface, bed shear stress distribution and helical flow strengths were compared. Verification using experimental measurements on a uniform bend showed that the numerical model can successfully simulate flow fields in bends. Results indicate that in a divergent bend, the path of maximum velocities at plane near water surface crosses the channel’s center line at about 50, while in uniform bends this occurs at about 55. Also the path of maximum velocity tangent to outer wall of uniform bend at about 90- 100, while in divergent bend occurs at about 80. The range of changes in height of water surface has increasing trend in the divergent channel in adverse of uniform bend and the maximum strength of helical flow is 10.55% larger than the uniform bend. Also, an additional secondary circulation cell at 135 is present in the divergent and uniform bends.